Post-graduate medical education in the time of COVID-19: Not a remotely simple task - Romeo, Giulio R.; Shaikh, Yousaf A.; Middelbeek, Roeland J. W. (Frontiers in Endocrinology, 2022)
The COVID-19 pandemic has stimulated a rapid shift towards telemedicine, which has had tremendous repercussions on all domains of the healthcare ecosystem. The effects of the transition to telemedicine on post-graduate medical education and on patient care provided by trainees have not been fully elucidated. Focusing on the multifaceted scope of endocrinology teaching clinics, the experience garnered by endocrinology fellows, preceptors, and patients through the adoption of virtual visits has shed new light on relevant challenges that require specific attention. First, we identified a divergent trend in glycated hemoglobin in people with type 1 diabetes according to their use of continuous glucose monitoring (CGM). Second, the patient’s perspective highlighted positive aspects, including expanded options for clinical care, but also limitations in communication with clinicians for people without access to videoconferencing tools or EHR-based portals. Finally, regarding medical training evaluation and skills-based learning, academic centers, professional organizations, and clinical educators should develop new teaching curricula suitable for a telemedicine-based environment. While simultaneously facing numerous pressures, fellows can potentially spearhead new models of care delivery and innovative approaches to clinical education leveraging telemedicine.